Immature reticulocyte fraction is an early predictor of bone marrow recovery post chemotherapy in patients with acute leukemia - Raja-Sabudin A.R.-Z.; Othman A.; Ahmed-Mohamed K.-A.E.; Ithnin A.; Alauddin H.; Alias H.; Abdul-Latif Z.; Das S.; Abdul-Wahid F.S.; Hussin N.H. (Saudi Arabian Armed Forces Hospital, 2024)
Indexed by WOS/SCOPUS